The Application of Sārāṇīyadhamma Principles to Strengthen The Community Network for Preserving Tai Lue Culture in Ban Thi Subdistrict, Ban Thi District, Lamphun Province. - Jiraeattanametea(Kammeunyongi) ่jirapong (MCU Haripunchai Review, 2025)
This article aims to: 1) Study the level of community network building for the preservation of “Tai Lue” culture;. 2)Compare public opinions regarding the strengthening of the community network for preserving “Tai Lue” culture, categorized by personal factors;. 3)Propose guidelines for strengthening the community network for cultural preservation of “Tai Lue” through the application of the six principles of Saraniyadhamma.The research employed a mixed-methods approach. The population consisted of residents in the Ban Thi Subdistrict Municipality. The sample group included 358 people. The research instrument was a questionnaire with a reliability coefficient of 0.810. Data were analyzed using frequency, percentage, mean, standard deviation, t-test, and F-test. The qualitative research component involved in-depth interviews with 12 key informants and content analysis. The research results found that: 1)The overall level of public opinion regarding the strengthening of the community network for “Tai Lue” cultural preservation was high. 2) Comparison of public opinion across variables such as gender, age, education level, occupation, and membership duration showed no significant differences. Thus, the research hypothesis was rejected. 3) The proposed guidelines for strengthening the community network for “Tai Lue” cultural preservation based on the six principles of Saraniyadhamma include: Physical acts of kindness (Metta-kaya-kamma): Building good relationships within the community.Verbal acts of kindness (Metta-vaci-kamma): Using meaningful and beneficial speech.Mental acts of kindness (Metta-mano-kamma): Encouraging network members to consistently forgive one another.Sharing of resources (Sadharana-bhogi): Promoting equity in communal use of resources.Moral harmony (Sila-samannata): Encouraging respectable behavior and discipline in the community. Viewpoint harmony (Ditthi-samannata): Allowing members to provide feedback and suggestions for development.